Multifunctional Mitochondrial Epac1 Controls Myocardial Cell Death. Issue 4 (17th February 2017) - Fazal, Loubina; Laudette, Marion; Paula-Gomes, Sílvia; Pons, Sandrine; Conte, Caroline; Tortosa, Florence; Sicard, Pierre; Sainte-Marie, Yannis; Bisserier, Malik; Lairez, Olivier; Lucas, Alexandre; Roy, Jérôme; et al.
Abstract : Rationale: : Although the second messenger cyclic AMP (cAMP) is physiologically beneficial in the heart, it largely contributes to cardiac disease progression when dysregulated. Current evidence suggests that cAMP is produced within mitochondria. However, mitochondrial cAMP signaling and its involvement in cardiac pathophysiology are far from being understood. Objective: : To investigate the role of MitEpac1 (mitochondrial exchange protein directly activated by cAMP 1) in ischemia/reperfusion injury. Methods and Results: : We show that Epac1 (exchange protein directly activated by cAMP 1) genetic ablation ( Epac1 −/− ) protects against experimental myocardial ischemia/reperfusion injury with reduced infarct size and cardiomyocyte apoptosis. As observed in vivo, Epac1 inhibition prevents hypoxia/reoxygenation–induced adult cardiomyocyte apoptosis. Interestingly, a deleted form of Epac1 in its mitochondrial-targeting sequence protects against hypoxia/reoxygenation–induced cell death. Mechanistically, Epac1 favors Ca 2+ exchange between the endoplasmic reticulum and the mitochondrion, by increasing interaction with a macromolecular complex composed of the VDAC1 (voltage-dependent anion channel 1), the GRP75 (chaperone glucose-regulated protein 75), and the IP3R1 (inositol-1, 4, 5-triphosphate receptor 1), leading to mitochondrial Ca 2+ overload and opening of the mitochondrial permeability transition pore. In addition, our findings demonstrate that MitEpac1 inhibits isocitrate dehydrogenase 2 via the mitochondrial recruitment of CaMKII (Ca 2+ /calmodulin-dependent protein kinase II), which decreases nicotinamide adenine dinucleotide phosphate hydrogen synthesis, thereby, reducing the antioxidant capabilities of the cardiomyocyte. Conclusions: : Our results reveal the existence, within mitochondria, of different cAMP–Epac1 microdomains that control myocardial cell death. In addition, our findings suggest Epac1 as a promising target for the treatment of ischemia-induced myocardial damage. Abstract : Supplemental Digital Content is available in the text.